Satellite Media Broadcasting with Adaptive Coding and Modulation. (2nd September 2009) - Gardikis, Georgios; Zotos, Nikolaos; Kourtis, Anastasios
Abstract : Adaptive Coding and Modulation (ACM) is a feature incorporated into the DVB-S2 satellite specification, allowing real-time adaptation of transmission parameters according to the link conditions. Although ACM was originally designed for optimizing unicast services, this article discusses the expansion of its usage to broadcasting streams as well. For this purpose, a general cross-layer adaptation approach is proposed, along with its realization into a fully functional experimental network, and test results are presented. Finally, two case studies are analysed, assessing the gain derived by ACM in a real large-scale deployment, involving HD services provision to two different geographical areas.